Innovation Management in Companies: a Multilevel Approach - Seclén, Jean Pierre (2016)
In this paper, we analyse the importance of innovation management in companies. The multilevel approach allows us to understand the phenomenon of innovation both from the perspective of the business manager and the policy maker, since the innovation ecosystem appears to play a key role in promoting innovative capacity in a given territory. While management models of innovation have changed over time, most of them have focused on large industrial enterprises without taking into account SMEs in general and micro-enterprises in particular, making it necessary to perform further studies on the innovation capacity of companies with this size.